Escritura y duelo en El limonero real de Juan José Saer - François Degrande (Caravelle)
This article aims to characterise the tension surrounding the concept of mourning in El limonero real (1974), the fourth novel of Argentinian writer Juan Joé Saer (1937-2005). With the anthropology of mourning as our theoretical framework, we try to demonstrate that the darkest of Saer’s novels displays all the conflicting traits of the enigmatic relationship between incorporation and introjection (Abraham and Torok). The present study also lays emphasis on Saer’s El limonero real as a powerfully innovative piece of work: the author successfully orchestrated a pathological fusion between, on the one hand, repetitive poetic prose inspired by nouveau roman objectivism and, on the other, psychoanalytic objectivation.